Imidazolium‐Functionalized Chemically Robust Ionic Porous Organic Polymers (iPOPs) toward Toxic Oxo‐Pollutants Capture from Water. Issue 53 (6th August 2021) - Sen, Arunabha; Dutta, Subhajit; Dam, Gourab K.; Samanta, Partha; Let, Sumanta; Sharma, Shivani; Shirolkar, Mandar M.; Ghosh, Sujit K.
Abstract: Fabricating new and efficient materials aimed at containment of water contamination, in particular removing toxic heavy metal based oxo‐anions (e. g. CrO4 2−, TcO4 − ) holds paramount importance. In this work, we report two new highly stable imidazolium based ionic porous organic polymers ( i POPs) decorated with multiple interaction sites along with electrostatics driven adsorptive removal of such oxo‐anions from water. Both the i POPs (namely, i POP‐3 and i POP‐4) exhibited rapid sieving kinetics and very high saturation uptake capacity for CrO4 2− anions (170 and 141 mg g −1 for i POP‐3 and i POP‐4 respectively) and ReO4 − (515.5 and 350.3 mg g −1 for i POP‐3 and i POP‐4 respectively), where ReO4 − anions being the non‐radioactive surrogative counterpart of radioactive TcO4 − ions. Noticeably, both i POPs showed exceptional selectivity towards CrO4 2− and ReO4 − even in presence of several other concurrent anions such as Br −, Cl −, SO4 2−, NO3 − etc. The theoretical binding energy calculations via DFT method further confirmed the preferential interaction sites as well as binding energies of both i POPs towards CrO4 2− and ReO4 − over all other competing anions which corroborates with the experimental high capacity and selectivity of i POPs toward such oxo‐anions. Abstract : An example of utilization of imidazole‐functionalized chemically robust cationic porous organic polymers (POPs) for rapid and efficient capture of hazardous dual oxo‐anionic pollutants from water. The study will enrich the concept of designing new efficient cationic polymeric materials to tackle the problems based on water pollution, one of the most important threats towards the initiative for a green and clean environment.